PENERAPAN MODEL ASSURE DENGAN MENGGUNAKAN MEDIA POWER POINT DALAM PEMBELAJARAN BAHASA INGGRIS SEBAGAI USAHA PENINGKATAN MOTIVASI DAN PRESTASI BELAJAR SISWA KELAS X MAN SUKOHARJO TAHUN PELAJARAN 2012/2013 - Achmadi, Heri (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
There are still many shortcomings and is not optimal in the learning process. Teachers as professionals are supposed to find and fix the learning process that used to be the assumption that learning English difficult and boring can be eliminated, otherwise can increase students motivation to learn English, so researcher applying one of which is the application of the model using the ASSURE Model and Powerpoint media.The subject of this research was X grade students of MAN Sukoharjo senior high school academic year 2012/2013, consisting of 21 students. This research was conducted at state in. Types of research used in this study are: CAR (Classroom Action Research). The researcher conducted three cycles of action research and each cycle consisted of a series of steps, namely: identifying the problems, planning the action, implementing the action, observing the action, reflecting the observation result, and revising the plan. The data of the research were collected by using some techniques including observation, interview, documents, and tests. Then, the qualitative data were analyzed by Interactive Model: data reduction, data display, and conclusion drawing or verification. The quantitative data were analyzed by using descriptive statistics (DS) to calculate the mean score of pretest and post-tests 1, 2, and 3.The results of the research was score: pretest 64;test on Cycle 1 68;test on Cycle 2 74;test on Cycle 3 79,52. This post test is higher than the English passing grade (KKM/ Kriteria Ketuntasan Minimal) that is 70. According the results above, the researcher can get the conclusions are:(1) In applying the ASSURE Model is a model that is strongly influenced by the teachers creativity in integrating the materials, methods, and media. (2) In model ASSURE students are also given the opportunity to evaluate himself, teachers, and schools, so that the implementation needs to support all components of the school. (3) Teachers are advised to master the concept of learning by ASSURE Model. Keywords:Model ASSURE,Powerpoint media,Students Achievement, Students Motivations